Public speaking training for the Sumatran rural young generation - Alamsyah Alamsyah; Muhammad Izzudin; Erlisa Saraswaty; Annada Nasyaya; Retna Mahriani (Universitas Muhammadiyah Magelang, 2023)
The young generation in rural South Sumatra has limitations in honing their confidence to appear in public. This condition made the Sriwijaya University FISIP Service team move to provide knowledge related to public speaking so that the young generation in rural South Sumatra, especially youth groups in Kandis Sub-district could rise up. This activity was held in September 2022 in the Kandis Village Office Hall, Ogan Ilir Regency, South Sumatra, which followed by 37 participants from Kandis District. The results of the training showed that there was an increase in the understanding and skills of the participants in public speaking